Adenovirus-α-Defensin Complexes Induce NLRP3-Associated Maturation of Human Phagocytes via Toll-Like Receptor 4 Engagement - Karsten, Eichholz (American Society for Microbiology, 2022)
Intramuscular delivery of human adenovirus (HAdV)-based vaccines leads to rapid recruitment of neutrophils, which then release antimicrobial peptides/proteins (AMPs). How these AMPs influence vaccine efficacy over the subsequent 24 h is poorly understood. In this study, we asked if human neutrophil protein 1 (HNP-1), an α-defensin that influences direct and indirect innate immune responses to a range of pathogens, impacts the response of human phagocytes to three HAdV species/types (HAdV-C5, -D26, -B35). We show that HNP-1 binds to the capsids and redirects HAdV-C5, -D26, and -B35 to Toll-like receptor 4 (TLR4), which leads to internalization, an NLRP3-mediated inflammasome response, and interleukin 1 beta (IL-1β) release. Surprisingly, IL-1β release was not associated with notable disruption of plasma membrane integrity. These data further our understanding of HAdV vaccine immunogenicity and may provide pathways to extend the efficacy.